In vitro acaricidal activity of several natural products against ibex-derived Sarcoptes scabiei - Pérez Pérez, María Jesús (2024)
In this study we analysed the effect of the temperature, diverse strains of Bacillus thuringiensis, Lysinibacillus sphaericus and nanoformulations with essential plant oils (EONP) on the survival of Sarcoptes scabiei mites derived from naturally-infested Iberian ibex (Capra pyrenaica). In general, mites maintained at 12ºC survived more than those maintained at 35ºC (40.7 hr and 31.2 hr, respectively). Mites with no treatment survived 27.6 h on average. Mites treated with B. thuringiensis serovar. konkukian and geranium EONP showed significant reduction in their survival. Despite the fact that these agents seem to be promising candidates for controlling sarcoptic mange in the field, further research is still needed to get stable, efficient and eco-friendly acaricides.